Some aspects of meromorphic fu nctions whose certain differential polynomials share a set. - Rajeshwari. S , Bhuvaneshwari. T, Chethan Kumar S, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article deals with the most important and interesting topic of Nevanlinna theory that is subject on the unicity problem of the power of a meromorphicfunctionswhosedifferentialpolynomialsshareasetwithitsderivative. The results which wegotinthissurveyistheimprovedandgeneralizedresultsofMengandLi[10].